Invasive trees rely more on mycorrhizas, countering the ideal-weed hypothesis - Moyano, Jaime (2021)
The ideal-weed hypothesis predicts that invasive plants should be less dependent on mutualisms. However, evidence in favor of or against this hypothesis comes mainly from observational studies. Here, we experimentally tested this hypothesis using a two-factor greenhouse experiment, comparing the seedling growth response of different Pinus species (varying in invasiveness) to ectomycorrhizal fungal inoculation. Most species showed no response until they were 6 mo old, at which point inoculation increased growth between 10 and 260% among the different species. This growth response was higher for species with lower seed mass, higher dispersal ability, higher Z score (a proxy for invasiveness) and higher number of naturalized regions, all of which correspond to higher invasiveness. Our results show that timing is a crucial factor when comparing mycorrhizal dependency of different species. Dependence on mutualistic microorganisms could be part of a strategy in which invasive species produce smaller seeds, in greater number, which can disperse further, but where seedlings are more reliant on mycorrhizas to improve access to water, nutrients, and protection from pathogens. Our results suggest that reliance on mutualisms may enhance, rather than limit, nonnative species in their ability to spread, establish, and colonize.